(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2020)
The essay aims at offering a journey within the documentary heritage of contemporary Italian women filmmakers, a survey drawing a varied map of approaches to the film medium, which take part in the redefinition process of cinema and its paradigms. The movies of these female directors deploy an exemplary commitment to (audio)visually exploring places, both central and peripheral, pointing out their nomadic vision and an itinerant gaze upon the world that is able to capture the current challenges and complexities with passion and rigour. Their works modulate in an original way the relationship between authorial intervention and social, cultural, historiographical investigation. Moreover, they propose a viewing on the most opaque and elusive sides of the contemporary realities, an observation that overall constitutes an innovation in the field of cinema as well as a change in the image of women, who are fully subjects of history, culture, and agency.